PENGARUH INSTITUTIONAL OWNERSHIP TERHADAP FINANCIAL PERFORMANCE MELALUI CAPITAL STRUCTURE SEBAGAI VARIABEL INTERVENING PADA NONMANUFAKTURING COMPANY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Claudia Hermanto; Josua Tarigan (Business Accounting Review, 2018)
In general a firm established with the intention to increase the value of the company. The purpose of this study was to examine the effect of institutional ownership towards financial perdormance of a firm throuhg capital structure as mediating on non manufacturing company that listed on the Indonesia Stock Exchange 2011-2015. Based on purposive sampling method, 90 samples were used as samples. This research uses WarpPLS analysis technique. The statistical result states that institutional ownership has positive significant on financial performance, institutional ownership has positive significant on capital structure, capital structure has negative significant on financial performance